A Study on the Physiological Activity of Stem Cell-Derived Conditioned Medium and Its Application for Cosmetic Materials - Moon, Ji-Sun; You, Seon-hee; Yoon, Mi-Yun (International Journal of Psychosocial Rehabilitation, 2020)
Background: According to a study on the efficacy of fat derived stem cell culture on skin regeneration, an increase in collagen synthesis was observed when stem cell culture was applied to fibroblasts and keratinocytes. In this study, the authors tried to identify the anti-aging effect of fat derived stem cell cultures through intracellular mechanism of action on skin cells. Methods: In order to confirm the physiological activity potential of stem cell culture, skin cell activity test was performed to determine the toxicity, collagen production inhibitory activity, and MMP-1 expression. Findings: Cytotoxicity was not identified at all concentrations, it was confirmed that the collagen production increased by about 20% compared to the control group without the sample treatment, MMP-1 expression through JNK and ERK signaling pathway even at low concentration. Improvements: In this study suggest that fat-derived stem cell cultures are not toxic when used and may be useful as functional cosmetic materials with anti-aging effects.